DARI GLOBAL KE DOMESTIK: PERIKANAN DAN EKONOMI PERIKANAN DI KARESIDENAN TERNATE, 1860-an-1920-an - , Umar Hi Rajab, Drs. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This thesis examines factors which caused the stagnation and static development in fisheries activity in the Residency of Ternate during the period 1860s â 1920s. The economy of the people in the coastal area is dualistic in character. The people depended their live in agriculture as well as fishery. The objective of this study is to scrutinize the response of fisherman towards changing technology in fishery and the state involvement in the economy if fishery. This study employs historical method by using primary sources, such as archives, and secondary sources such as articles, book, journals and so on. The main problem in this study is the changing of orientation economic fishery from global to domestic consumption, and the stagnation of application of technology. Based on the available data shows that the static development in economic fishery was caused by the lack of response from government. The fishery which was not the main colonial economic activity in Ternate was let alone to remain in the outskirts of economy. It was composed based on tradition and local mentality and static in development, either in production as well as application of technology. During the period covered in this study, the significant changing was only happen in social aspect. Finally the study concludes that fishery activity during this period is static and still traditional. The non-existence of state and serious effort in handling fishery economy caused the changing orientation of the fishery economy from global to domestic market.